The Model of Job Satisfaction and Employee Performance - Marthina Berliana; Nahar Siregar; Huske Dwi Gustian (International Review of Management and Marketing, 2018)
Environmental conditions are increasingly rapid changes and uncertain, demanding an organization, both private, government and BUMD to anticipate these changes, in order to maintain its survival. PT.ABC is no exception, which must be able to serve the community as well as possible, so that employees always strive for their employees to act and work in accordance with the organizational culture so that this company can carry out its vision and mission optimally. The low performance of employees in addition to problems Remuneration compensation, allegedly also due to work satisfaction problems, because remuneration compensation and job satisfaction can provide strong encouragement or motivation for employees to work optimally to achieve high performance. The purpose of this study was to determine and analyse: (1) compensation for remuneration (2) job satisfaction; (3) performance; and (4) the effect of remuneration compensation and job satisfaction on the performance of PT.ABC employees, both simultaneously and partially. The research method used in this research is descriptive survey and explanatory survey, the unit of analysis in this study is the staff in the PT.ABC neighbourhood with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the remuneration compensation given was considered quite appropriate, job satisfaction was considered satisfied, employee performance was considered high, remuneration compensation had an effect on job satisfaction, and remuneration compensation and job satisfaction had an effect on employee performance among remuneration compensation and employee performance satisfaction affect performance, it turns out that remuneration compensation has a dominant influence Because remuneration compensation has a dominant influence on performance rather than job satisfaction, it is advisable to provide appropriate remuneration compensation by increasing other benefits which, so that employees are able to work more professionally.